Pengaruh Kepemimpinan Dan Motivasi Terhadap Kepuasan Kerja Karyawan Pada Indomaret Area Rawa Buntu - Deka Harisma; Melda Wiguna (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to examine the influence of leadership and motivation on employee job satisfaction at PT Indomarco Prismatama, Rawa Buntu Area, both individually (partial) and collectively (simultaneous). The research employed a quantitative approach using a sample of 55 employees. The data analysis procedures included validity and reliability testing, normality testing, multicollinearity testing, autocorrelation testing, heteroscedasticity testing, simple linear regression analysis, multiple linear regression analysis, simple and multiple correlation analyses, coefficient of determination analysis, t-test, and F-test. The findings indicate that, partially, leadership has a positive and significant effect on employee job satisfaction, as demonstrated by a t-value of 6.392, which exceeds the critical t-value of 2.005, along with a significance level of 0.000 < 0.05. Similarly, motivation shows a positive and significant effect on job satisfaction, supported by a t-value of 6.826 > 2.005 and a significance level of 0.000 < 0.05. Furthermore, the results of the F-test reveal that leadership and motivation simultaneously exert a significant influence on job satisfaction, reflected in an F-value of 34.777, which is greater than the critical F-value of 3.17, with a significance level of 0.000 < 0.05. In conclusion, both leadership and motivation, whether assessed partially or simultaneously, significantly contribute to enhancing employee job satisfaction at PT Indomarco Prismatama, Rawa Buntu Area.